Prinsip Kompensasi Dalam Prespektif Islam - Efrita Norman; Rio Kartika Supriyatna; Dedi Junaedi (LPPM Institut Nasional Laa Roiba Bogor, 2021)
Compensation is important for employees and the sustainability of a company, no wonder this is a conversation every year where we know that March 1 is celebrated as national labor day, on that date employees or workers demand an increase in compensation / wages so that this becomes the problem for employees and companies where employees want high wages while companies want low payments to their employees, this phenomenon does not only occur at the regional level but at the national and even international levels, so the author tries to present a solution for companies in paying wages to their employees using the principle Islamic principles. This research is a qualitative research using the literature study method, and from the Koran & Sunnah where researchers study the Koran, Sunnah and literature published by journals and magazines in this field. The results of compensation management research in an Islamic perspective are that there are several principles that must be considered and possessed by every company owner including being honest, trustworthy, able to work together, can provide fair compensation, have a sense of brotherhood and fulfill the agreed contract. In addition, there are also principles that must be possessed by every employee, including the principles of discipline, dedication and sincerity so that if this is owned by the company and every employee, satisfaction between the two will be achieved.